From Promise to Performance: The Environmental Impact of Green Bond Issuance on Corporate Emissions - Jisland,Hugo; Henriksson,Tom (2025)
This thesis examines whether corporate green bond issuance leads to measurable improvements in environmental performance among European firms in high-emitting sectors. Using firm-level panel data from 2015–2022, we match green bond issuers with conventional bond issuers using nearest-neighbour matching with Mahalanobis distance. Employing a difference-in-differences approach, we analyse changes in greenhouse gas (GHG) emissions at two and three years post-issuance. Our results indicate that green bond issuance is associated with a statistically significant reduction in emissions intensity compared to conventional bond issuance. Further, only bonds certified by a third party exhibit a significant impact on emissions; non-certified bonds show no clear effect, highlighting ongoing greenwashing concerns. These findings suggest that green bonds can contribute to decarbonisation, but the environmental benefits depend on credible certification. The study provides new evidence on the real-world effectiveness of green bonds and underscores the importance of robust verification standards in sustainable finance.
Keywords: green bonds; corporate green bonds; green bond issuance; emissions intensity